Uji Lanjutan Isolasi dan Identifikasi Bakteri pada Bioaktivator dari Limbah Bonggol Pisang (MOL) dalam Proses Pengomposan Sampah Organik Rumah Tangga - Dini Yuliansari; Enida Fatmalia (Bioscientist : Jurnal Ilmiah Biologi, 2020)
One of the factors of plant fertility is influenced by the addition of compost which contains bioactivators. One of the bioactivators that can be used in the composting process traditionally is using MOL (Local Microorganisms). MOL from banana stem is an alternative material that can be used as a starter in the composting process. This study aims to isolate and identify N-fixing bacteria and phosphate solvents that work in the composting process of household organic waste using banana steam waste as MOL for bioactivators. This research is experimental. The making sample of MOL and the process of bacterial isolation were carried out in the STTL Mataram Laboratory, then identification of the type of bacteria was carried out at The Balai Laboratorium Kesehatan dan Kalibrasi. The results showed that the bacteria identified in the MOL sample were Pseudomonas sp. and Citrobacter freundii.